Permainan Berburu Harta Karun dalam Meningkatkan Kemampuan Sosial Emosional Anak - Ayu Nabila; Taufiqurrahman Taufiqurrahman; Ulfah Amini (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
The objective of this study was to enhance the social-emotional abilities of Group A children at RA Annidhomiyah in Cirebon Regency through the activity of a treasure hunt game. The research method used was classroom action research, with data collection through observation and documentation during the research process. Data analysis was conducted qualitatively through data triangulation and observation persistence, while quantitative data analysis utilized class averages and percentages. The results of the study showed that prior to the intervention, the social-emotional abilities of Group A children at RA Annidhomiyah in Cirebon Regency had not reached the expected developmental level. However, after implementing the treasure hunt game activity, there was a significant improvement in the social-emotional abilities of these children. The improvement in social-emotional abilities was evident from the obtained results. In the pre-cycle stage, only about 28% achieved the expected lower limit. However, this increased to 55% in the first cycle. After improvements were made in the second cycle, there was an 83% increase in social-emotional abilities, surpassing the minimum achievement level set in this study, which was ? 80%. Therefore, the intervention was stopped in the second cycle as it was considered successful. In conclusion, it can be inferred that through the activity of a treasure hunt game, there was an enhancement in the social-emotional abilities of Group A children at RA Annidhomiyah in Cirebon Regency.